Association of TNFSF15 polymorphism with irritable bowel syndrome. Issue 12 (2nd June 2011) - Zucchelli, Marco; Camilleri, Michael; Nixon Andreasson, Anna; Bresso, Francesca; Dlugosz, Aldona; Halfvarson, Jonas; Törkvist, Leif; Schmidt, Peter T; Karling, Pontus; Ohlsson, Bodil; Duerr, Richard H; Simren, Magnus; et al.
Abstract : Background: Irritable bowel syndrome (IBS) is the most common gastrointestinal disorder, affecting more than 10% of the general population worldwide. Although a genetic component is suspected, unambiguous susceptibility genes have so far not been identified. This study tested the hypothesis that genes contributing to epithelial barrier integrity, control of mucosal immune responses and interactions with bacteria in the gut are associated with IBS. Methods: Single nucleotide polymorphisms (SNPs) corresponding to top signals of association with Crohn's disease at 30 known susceptibility loci were tested for their effect on IBS risk in 1992 individuals from two independent case–control cohorts from Sweden and the USA. Association tests included a conservative Bonferroni correction for multiple comparisons, and were also performed on specific subgroups of patients characterised by constipation (IBS-C), diarrhoea (IBS-D) or alternating constipation and diarrhoea (IBS-A). Results: The Crohn's disease risk allele rs4263839 G in the TNFSF15 gene was significantly associated with an increased risk of both IBS (p=2.2×10 −5 ; OR 1.37) and more pronouncedly, IBS-C (p=8.7×10 −7 ; OR 1.79) in the entire sample. Similar associations and risk effects of the same magnitude were observed in the two cohorts analysed separately. A correlation between rs4263839 genotype and TNFSF15 mRNA expression was detected both in peripheral blood and in rectal mucosal biopsies from healthy individuals (combined p=0.0033). Conclusions: TNFSF15 is a susceptibility gene for IBS and IBS constipation. As TL1A, the protein encoded by TNFSF15, contributes to the modulation of inflammatory responses, the results support a role of immune activation in IBS.